Partisipasi Masyarakat Dalam Menciptakan Kampung Tangguh Nasional (Studi Kasus Desa Lueng Ie Aceh Besar) - Mukhrijal Mukhrijal; Afrijal Afrijal; Arneta Aulia; Nabilah Azzahra Putri; Darkasyi Putra; Andika Hazli Kautsar (Jurnal Pemerintahan dan Politik, 2023)
National Tangguh Village is a program held in leng ie Village, Kec. Krueng Barona Jaya, Kab. Aceh Besar which aims to create a village on a national scale. The programs are carried out by the government of Lueng Ie Village, Krueng Barona Jaya District, Kab. Aceh Besar is the existence of the Poskesdes Program where the activities carried out at the Poskesdes are Posyandu. Then there is also the construction of rental houses built by the village government to increase the income of Lueng Ie Village. In this case the village government of Lueng Ie has an important role to socialize this program to the community. And the community also has a role that is no less important to participate in the success of the program. But in reality the people of Lueng Ie Village are not participating due to the lack of information about the National Tangguh Village Program and the relatively low HR factor.